Campaign of 1958 on Literacy Eradication in Ulyanovsk Region as Reflection of Socio-Cultural Policy of USSR in Period of N. S. Khrushchev’s Transformations - O. R. Khasyanov (Научный диалог, 2018)
The subject of the study is the fight against illiteracy in the RSFSR during the Khrushchev “Thaw.” Based on the analysis of scientific literature and archival documents, which are first introduced into scientific circulation, the process of completing the fight against illiteracy among the adult population of the Ulyanovsk region in the framework of the 1958 campaign is reconstructed. The object of the study is the methods, mechanisms and practices of regional authorities aimed at reducing the number of illiterate population of the Ulyanovsk region. According to the author, N. S. Khrushchev’s social policy, in particular the fight against illiteracy, is an integral part of the Soviet modernization project. The analysis of archival documents and research materials allowed to conclude that the campaign of 1958 on the literacy eradication had political and largely formal nature. It is reported that the district authorities transferred full responsibility for the implementation of the basic provisions of the special decree on the elimination of illiteracy among the population to the institute of education. It is emphasized that the authorities did not provide real assistance to schools. It is shown that, in turn, the teacher, seeing the lack of interest of the authorities, performed their functions in the field of education of illiterate population formally, in some cases, teachers made fictitious acts of completion of the educational process with illiterate population. It is proved that the party instances underestimated the real number of illiterate population.